Direct Photocoagulation Guided by Merged Retinal Images for the Treatment of Focal Diabetic Macular Edema - Yoshihiro Takamura; Takehiro Matsumura; Shogo Arimura; Makoto Gozawa; Masakazu Morioka; YutakaYamada; Masaru Inatani (International Journal of Endocrinology)
Purpose. To introduce a novel laser photocoagulation (PC) protocol named merged image-guided PC (MIG-PC), which included merging the images of the fundus, optical coherence tomography (OCT) map, and fluorescein angiography (FA). We compared the anatomical and functional results between MIG-PC and FA-guided PC (FG-PC) for the treatment of focal diabetic macular edema (DME). Method. We examined the treatment outcomes in 27 consecutive eyes treated with MIG-PC compared with 28 matched eyes treated with FG-PC. We identified the microaneurysms (MAs) located in the focal edema areas and ablated them using focal PC. Best-corrected visual acuity (BCVA) and retinal thickness (RT) measured using OCT were compared between the groups at baseline and 2, 4, 8, 12, and 24 weeks after treatment. Results. The foveal and perifoveal RT were reduced after treatment in both the groups, and the perifoveal RT in the MIG-PC group was significantly lower than that in the FG-PC group at 4 weeks and thereafter. BCVA in the MIG-PC group was significantly higher than that in the FG-PC group at 12 and 24 weeks. The numbers of laser spots (p=0.0001), additional laser treatments (p=0.0121), and intravitreal injection of ranibizumab (p=0.0012) in the MIG-PC group were significantly lower than those in the FG-PC group (Mann–Whitney test). Conclusion. MIG-PC contributed to the improvement in BCVA and reduction in RT, number of laser shots required, and retreatment rates. Based on our data, MIG-PC can be recommended for the treatment of focal DME. This trial is registered with ID UMIN000030390.